ADSORPTION OF METHYLENE BLUE ONTO RAW SECONDARY SEWAGE SLUDGE: ISOTHERM, KINETIC, AND CHARACTERIZATION STUDIES - KHATRI, Ilhaam; TAMBI, Ashish; RAJAWAT, Deepak Singh (Studia Universitatis Babeș-Bolyai Chemia, 2026)
The increased discharge of synthetic dyes into aquatic ecosystems has caused significant environmental concerns, prompting the search for sustainable adsorbents. Sewage sludge, an abundant by-product of wastewater treatment facilities, offers the opportunity for dye removal within a circular economy paradigm. This study investigates the potential of raw dried secondary treated sewage sludge as an effective adsorbent for the removal of methylene blue, a cationic dye, from aqueous solutions. The adsorbent was characterized by Fourier transform infrared spectroscopy, field emission scanning electron microscopy, and Brunauer–Emmett–Teller surface analysis to evaluate its morphology, functional groups and textural properties. Batch adsorption experiments examined the effects of pH, initial dye concentration, adsorbent dosage, particle size, and contact time on the removal efficiency. Optimal conditions were observed at pH 9, with 0.5 g of sewage sludge (particle size 0.5 mm) in 50 mL of 10 mg/L dye solution and a contact time of 30 minutes. The adsorption equilibrium data conformed best to the Langmuir isotherm model, with a maximum monolayer adsorption capacity of 14.08 mg/g. Kinetic studies indicated that the adsorption process followed the pseudo-second-order model (R²=0.999), suggesting chemisorption as the predominant mechanism. The adsorbent also exhibited a pH-stabilizing behaviour, wherein the solution pH after adsorption shifted toward neutrality regardless of the initial pH, highlighting its suitability for practical wastewater treatment applications. The study demonstrates the potential of raw secondary treated sewage sludge as an eco-friendly adsorbent, aligning with sustainable wastewater treatment strategies.